Dislexia: uma reflexão sobre a formação docente e a atuação em sala de aula - Santos, Maria Aparecida dos (2017)
The present work presents a brief overview on dyslexia, presents constitutional precepts and brings a reflection on the formation of pedagogues in the sense of better attending the student with dyslexia. It is understood that the lack of information about dyslexia by educators can negatively impact the learning process of dyslexic students. Therefore, it is understood that the theme is relevant to the academic field in several aspects. The objective is, therefore, to reflect on the knowledge necessary for the teacher to act in front of the dyslexic student in the classroom. At first, we tried to base the study from several theoretical surveys, to better understand the subject. And, based on reports in the following works: Dyslexia and OtherReading Disorders - Writing by Jaime Zorzi and Simone Capelline (2009), Dyslexia, Speech and Language by Margaret Snowling and Joy Stackhouse, (2004) reprint (2008), Diagnosis And treatments of the learning problems of Sara Paín (1992), the film As a Star on Earth: every child is special, produced by Aamir khan (2007), Federal Constitution of 1988 among others, sought to collect concepts pertinent to dyslexia, With the purpose of elucidating some misunderstandings about the theme among other subjects related to the educational context. In the light of this, we set out for a critical reflection, based on the mentioned theorists and the film already mentioned, concerning the formation and the role of the teacher in front of the difficulties of the student. Therefore, it is understood that educating is not an easy task. In fact, academic trajectory, theoretical studies and research have revealed that there is a long way to go to meet the needs of dyslexic students adequately. It should therefore be born in mind that in order to succeed in the learning process, it is necessary to consider several reports pertinent to the reality of the learner as well as to the school universe in some aspects.